Is ZISWAF'S Institution Susceptible to Moral Hazard? : A Sentiment Analysis - Siti Fatimah Azzahro; Aufa (SMART Insight, 2022)
The purpose of this study is to identify attitudes about ZISWAF throughout the previous five years, from 2019 to 2023, and to determine whether or not moral hazard can exist at ZISWAF institutions. The technique involves using SentiStrength and Microsoft Excel 2019 to analyse secondary data in metadata from 149 journals collected from Dimensions, together with descriptive statistical analysis, meta-analysis, and sentiment analysis. The sentiment analysis's findings demonstrate the perspectives of ZISWAF researchers, with neutral sentiments representing for 41%, positive sentiments for 32%, and negative sentiments for 26%. ZISWAF-related research reveals a positive attitude since people are still optimistic about this financial instrument's potential to solve social issues. The fact that ZISWAF fund management still operates on a manual method, which is susceptible to moral hazard and human error, the ineffectiveness of ZISWAF management, and the lack of a supervisory institution for ZISWAF fund management all contributed to the unfavourable sentiment that was discovered in the research regarding to ZISWAF. As a further practical application, this study makes recommendations to regulators, academics, and the ZISWAF Institution.